2018
DOI: 10.1080/23794925.2018.1429228
|View full text |Cite|
|
Sign up to set email alerts
|

Impressions of “Evidence-Based Practice”: A Direct-to-Consumer Survey of Caregivers Concerned About Adolescent Substance Use

Abstract: National behavioral health organizations have recently started using direct-to-consumer (DTC) marketing strategies as a means of promoting increased utilization of evidence-based practice (EBP). Such strategies often encourage patients and caregivers to proactively seek out EBP, based on the assumptions that patients and caregivers understand the concept and view it favorably. We conducted a DTC marketing survey of caregivers concerned about their adolescents’ substance use in order to explore how these caregi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 22 publications
1
30
0
Order By: Relevance
“…Based on prior research with specific clinical populations (Becker et al, ; Carman et al, ; Tanenbaum, ), we hypothesized that a minority of MTurk adults would define EBMHC correctly and value scientific information in decision‐making. In addition, in light of health disparities experienced by racial/ethnic minority populations, and the finding by Becker, Weeks et al () that ethnic minority parents of adolescent substance users with lower educational attainment and lower per capita income were more likely to define evidence‐based therapy incorrectly, we predicted that knowledge and perceived importance of EBMHC in the present sample of internet‐using adults would vary as a function of ethnicity, educational attainment, and income. Finally, we expected that knowing the correct EBMHC definition would be associated with valuing scientific information and that both variables would be associated with mental health literacy.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Based on prior research with specific clinical populations (Becker et al, ; Carman et al, ; Tanenbaum, ), we hypothesized that a minority of MTurk adults would define EBMHC correctly and value scientific information in decision‐making. In addition, in light of health disparities experienced by racial/ethnic minority populations, and the finding by Becker, Weeks et al () that ethnic minority parents of adolescent substance users with lower educational attainment and lower per capita income were more likely to define evidence‐based therapy incorrectly, we predicted that knowledge and perceived importance of EBMHC in the present sample of internet‐using adults would vary as a function of ethnicity, educational attainment, and income. Finally, we expected that knowing the correct EBMHC definition would be associated with valuing scientific information and that both variables would be associated with mental health literacy.…”
mentioning
confidence: 84%
“…Similarly, Becker et al () found that consumers of adolescent substance use treatment were unfamiliar with the concept of evidence‐based therapy and had concerns that the approach seemed inflexible. Finally, two studies found that perceptions of and preferences for information about EBMHC vary according to consumer socio‐demographic and clinical characteristics such as education, race/ethnicity, income, and a history of treatment (Becker, Helseth, Frank, Escobar, & Weeks, ; S. J. Becker, Weeks et al, ).…”
mentioning
confidence: 99%
“…In their discussion of direct-to-consumer marketing of evidence-based anxiety treatments, Gallo et al (2013) argued that providers underuse evidence-based treatments and that consumers do not have knowledge about the effectiveness of these treatments. Recent research shows that there is a lack of knowledge regarding evidence-based psychotherapies among U.S. adults (Becker, Weeks, et al, 2018; Mora Ringle et al, 2019). Gallo and colleagues noted that with increased knowledge about treatment, consumers could create a market pull for treatments that work, ultimately pushing providers to provide these treatments.…”
Section: Discussionmentioning
confidence: 99%
“…There is much room for research in this area; in a recent study of U.S. adults in an online sample, only 20% could accurately define evidence-based mental health care (Mora Ringle et al, 2019). In a sample of parents concerned about their teens’ substance use, almost 70% reported wanting to hear about psychological treatments via the web (Becker, Helseth, Frank, Escobar, & Weeks, 2018), and most of these same parents also reported valuing evidence-based-practice principles (Becker, Weeks, et al, 2018). However, very little research has examined how to promote potential consumers’ engagement with information about evidence-based psychological treatments or how to best define it in terms that the public will appreciate.…”
mentioning
confidence: 99%
“…Study procedures have been reported elsewhere (Becker et al, 2018) and are briefly summarized here. The study was deemed exempt from the University institutional review board due to the lack of identifying information collected.…”
Section: Participants and Proceduresmentioning
confidence: 99%